An Empirical Study on Patients' Satisfaction with Healthcare Services of Community Clinics in Rural Bangladesh: Based on Exploratory Factor Analysis - Tasrun Jahan; Md. Shawkat Ali (Universitas Muhammadiyah Palu, 2025)
Analyzing patient satisfaction is crucial for assessing the performance and accessibility of health services in light of the rising demand for healthcare. The opinions of patients are becoming more and more weighted in the formulation of policies. The healthcare management in developing countries appears to have mainly disregarded patients' opinions of their countries' healthcare systems. Therefore, this study is patient-centered and aims to examine the factors influencing patients' satisfaction with healthcare services provided by community clinics in rural Kapasia, Bangladesh. A cross-sectional survey was conducted with 434 samples. Exploratory factor analysis was used to find the potential factors that might influence patient satisfaction. The results suggest that health staff explanation about medicine and dosages received the highest rating from respondents (3.86±.39) while the availability of drinking water received the lowest rating 1.93±0.68. The study has revealed that the 3 factors that affect the satisfaction of patients are health staff service attitude and basic amenities in the waiting area. To increase patient satisfaction, health administrators should prioritize the three aforementioned factors and put the right plans into action. The strategic steps required to address the demands of patients in the government healthcare sector are also discussed in the study’s conclusion.